Exploring Emergent Nanotechnology Applications in Mechanical and Health Engineering - Nobile, Lucio; Nobile, Stefano (Recent Patents on Mechanical Engineering, 2025)
Nanotechnology is a promising area of research in science and technology with potential benefits in automotive, aircraft, construction, energy, healthcare, agriculture, food processing, although it has its own risks in environmental sustainability. Recent advances in this area have stimulated research and their applications in different fields, with important results in mechanical engineering and health engineering. The aim of this article is to give an overview of some recent advances of nanotechnology, exploring emerging applications of these typical technologies. Examples of some successful practical applications and patents in mechanical and healthcare engineering based on this technology are given, and an analysis of the prospects and main problems of this area is also conducted. Furthermore, mechanical engineers and health professionals would find this review valuable in updating their knowledge on the latest developments in nanotechnology applications.
Keywords: nanodevise